Concurrent live imaging of DNA double-strand break repair and cell-cycle progression by CRISPR/Cas9-mediated knock-in of a tricistronic vector. Issue 1 (December 2018) - Otsuka, Kensuke; Tomita, Masanori
Abstract Cell-cycle progression can be arrested by ionizing radiation-induced DNA double-strand breaks (DSBs). Although DSBs are patched by DSB repair systems, which comprise proteins such as p53-binding protein 1 (53BP1), the relationship between DSB repair progression and cell-cycle status in living cells is unclear. The probe FUCCI (fluorescent ubiquitination-based cell-cycle indicator) was previously developed for visualizing cell-cycle status. Here, we established novel live-imaging probes based on custom-designed plasmids designated "Focicles" harboring a tricistronic compartment encoding distinct fluorescent proteins ligated to the murine 53BP1 foci-forming region (FFR) and two cell-cycle indicators that are known components of FUCCI (hCdt1 and hGmnn). We used CRISPR/Cas9-mediated genome editing to obtain Focicle knock-in cell lines in NIH3T3 cells, which were subject to X-ray irradiation that induced comparable numbers of Focicle and endogenous-53BP1 foci. In addition, the Focicle probes enabled the kinetic analysis of both DSB repair and cell-cycle arrest/progression after irradiation, demonstrating that the Focicle knock-in cells progressed to cell division after DNA damage elimination. These newly developed probes can help to gain a better understanding of the dynamics of DSB repair and cell-cycle control to in turn guide cancer treatment development and cancer-risk assessments.